GAMMA-400 experiment: perspectives of observation of the discrete astrophysical gamma-ray sources in the Milky Way disk. (February 2019) - Bakaldin, A V; Galper, A M; Leonov, A A; Suchkov, S I; Topchiev, N P
Abstract: The GAMMA-400 space experiment is aimed for the study of gamma rays in the energy range from ∼20 MeV up to several TeV. The observations will carry out with GAMMA-400 gamma-ray telescope installed onboard the Russian space observatory. GAMMA-400 has unique angular and energy resolutions for gamma rays with energy more than few GeV, which are significantly better than the Fermi-LAT ones. The orbit of the GAMMA-400 space observatory (near-Earth, circular with altitude about 200000 km) will be without the occultation by the Earth and outside the radiation belt. Thus it will be possible to carry out the continuous long-term observations of gamma-ray sources on the sky. In this work we present the expected statistics of gamma quanta that can be collected with GAMMA-400 from known discrete astrophysical gamma-ray sources in the disk of our galaxy during observations in orbit. 3FGL and 3FHL catalogs of discrete gamma-ray sources obtained in the Fermi experiment were used to calculate the number of gammas. It is shown that the accumulated statistics will allow us to carry out detailed investigation of characteristics (such as spatial distribution, energy spectrum, variability) of discrete gamma-ray sources in the Milky Way disk.